Pengaruh Pengalaman Kerja,Pendidikan dan Pelatihan Serta Prestasi Kerja Terhadap Pengembangan Karir Karyayawan - Ratna Imbun, Yohana; Prayekti, Prayekti; Ratna Purnamarini, Tri (Universitas Hamzanwadi, 2024)
The aim of this research is to understand the impact of work experience, level of education, training, and performance on a person's career development. This research uses a quantitative approach as the main method. Respondents in this study were active workers at PT. Nampar Nos Ruteng, East Nusa Tenggara, totaling 75 employees. Primary data is the main source in this research. Data quality evaluation was carried out using Validity Test, Reliability Test, and Classical Assumption Test. The data analysis methods used in this research are Multiple Linear Regression Analysis, t-Statistic Test, and F-Statistic Test. The results of this research show that at PT. Nampar Nos Ruteng, work experience does not have a significant impact on career development, because the t test produces a value of -2.044 with a significance level of 0.045, which is lower than 0.05. Likewise, education and training also do not have a significant effect on career development at PT. Nampar Nos Ruteng, because the t test shows a value of -1.332 with a significance of 0.187, which exceeds 0.05. However, work performance is proven to have a significant influence on career development at PT. Nampar Nos Ruteng, because the t test shows a value of 11.807 with a significance of 0.001, which is smaller than 0.05. Overall, work experience, education and training, and work performance have a significant impact on career development at PT. Nampar Nos Ruteng